2009
DOI: 10.1165/rcmb.2008-0102oc
|View full text |Cite
|
Sign up to set email alerts
|

Mutation of Murine Adenylate Kinase 7 Underlies a Primary Ciliary Dyskinesia Phenotype

Abstract: Primary ciliary dyskinesia (PCD) is a genetically and phenotypically heterogeneous disorder, characterized by progressive development of bronchiectasis, inflammation, and features characteristic of chronic obstructive pulmonary disease. We report here that a murine mutation of the evolutionarily conserved adenylate kinase 7 (Ak7) gene results in animals presenting with pathological signs characteristic of PCD, including ultrastructural ciliary defects and decreased ciliary beat frequency in respiratory epithel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
88
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(95 citation statements)
references
References 48 publications
7
88
0
Order By: Relevance
“…Ak7 (adenylate kinase 7): 30,66,71 Our findings were essentially identical to those recently reported by another group. 30 Grossly, all Ak7 -/-mutant mice exhibited domed heads and hydrocephalus.…”
Section: Ulk4 (Unc-51-like Kinase 4 [C Elegans])supporting
confidence: 92%
See 1 more Smart Citation
“…Ak7 (adenylate kinase 7): 30,66,71 Our findings were essentially identical to those recently reported by another group. 30 Grossly, all Ak7 -/-mutant mice exhibited domed heads and hydrocephalus.…”
Section: Ulk4 (Unc-51-like Kinase 4 [C Elegans])supporting
confidence: 92%
“…30 Grossly, all Ak7 -/-mutant mice exhibited domed heads and hydrocephalus. Histologically, the most notable lesions included moderate to severe hydrocephalus, which was accompanied by chronic active rhinosinusitis characterized -/-mouse.…”
Section: Ulk4 (Unc-51-like Kinase 4 [C Elegans])mentioning
confidence: 98%
“…37 Three AKs are now known to be associated with disease phenotypes, AK1 (OMIM 103000) causes chronic hemolytic anemia in humans, 38 AK2 (OMIM 267500) causes reticular dysgenesis in humans, 39 and AK7 (OMIM 615364) with primary ciliary dyskinesia in mice. 40 AK1, like AK9, is cytosolic and associated with mental retardation and psychomotor retardation. Taken together, AKs are disease genes and associated with specific phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have demonstrated motility as one of the main functions of cilia, and its impairment may cause severe phenotypes such as decreased ciliary beat frequency in the respiratory epithelium [13]. Ciliary motility is also required for brain development and function.…”
Section: Motility: Agents Of Cellular Movementmentioning
confidence: 99%